Time-dependent behavior of subcritical crack growth for rock plate: Experimental and numerical study. (November 2018) - Yuan, Haiping; Wang, Feng; Liu, Yan; Bian, Hanbing; Chen, Wen; Wang, Yixian
Time-dependent behavior of subcritical crack growth is one of the main characteristics in rocks. The double-torsion test is commonly used to study the slow crack growth behavior of brittle and quasi-brittle materials. However, double-torsion specimen is difficult to processing, the process of the laboratory test is irreversible, and the current numerical simulation is difficult to consider the time-dependent behavior, and so on. In view of all above problems, an idealized particle model was built, and the crack was identified in this article, based on the theory of particle flow. The numerical model was built using Particle Flow Code in 3 Dimensions, and the macromechanical and micromechanical parameters of the model were calibrated. The process of the macroscopic crack propagation and its evolution were analyzed. The intrinsic relations with the load, the displacement, and the time were established. The results show that the Particle Flow Code in 3 Dimensions can reproduce the time-dependent behavior of subcritical crack growth in double-torsion test. And, the peak and the law of the curves are in good agreement with the laboratory test results. Therefore, the Particle Flow Code in 3 Dimensions numerical simulation can be used as a new effective method to reveal the slow crack growth behavior, to get the relevant parameters such as V, KI, and KIC, and to build the relationship between V and KI . The results of this article will have some reference value for the simulation and application of double-torsion test.